DEVELOPING MOBILE LEARNING MANAGEMENT SYSTEM (MLMS) BASED ON ANDROID FOR CURRICULUM LITERACY - Riyana, Cepi (Edulib, 2018)
This research on instructional innovation aims to develop an application of Mobile Learning Management System (mLMS) based on Android Honeycomb as a medium for college students to increase their master of the basic professional course, with broader access and richer content packaged in multimedia. The problem under research is â€œHow does the development of a model mobile Learning Management System (mLMS) based on Android Honeycomb as studentsâ€™ learning medium improve the quality of the teaching learning and accessibility of basic professional courses, especially for the Curriculum and Instruction course in Universitas Pendidikan Indonesia? The research adopted the development model of Thiaragajan, SemÂmel, Semmel, consisting of â€œdefine, design, and develop.â€ The subjects were students taking the professional basic course of Curriculum and Instruction in the Department of Accounting Education A and Department of German Education B. The instruments used were online questionnaires and tests.The findings show: (1) The development of mobile Learning Management System (mLMS) based on Android Honeycomb was carried out through the stages of needs analysis of the model, development of conceptual framework, and development of software requirement; (2) The model of mobile Learning Management System (mLMS) based on Android Honeycomb consists of three stages, namely pre-learning activities, learning, and post learning; (3) The use of mobile Learning Management System (mLMS) based on Android Honeycomb was able to increase the learning outcomes in the course of Curriculum and Instruction in UPI. The increase can be seen in the post-test scores that were greater than the pre-test scores; and (4) Studentsâ€™ responses and perceptions of the use of the application of mobile Learning Management System (mLMS) based on Android Honeycomb in the course of Curriculum and Instruction in general were good and positive.